The Use and Potential of Biomedical Detection Dogs During a Disease Outbreak - Maughan, Michele N.; Best, Eric M.; Gadberry, Jenna Dianne; Sharpes, Caitlin E.; Evans, Kelley L.; Chue, Calvin C.; Nolan, Patrick Lawrence; Buckley, Patricia E. (Frontiers in Medicine, 2022)
Biomedical detection dogs offer unique advantages during disease outbreaks that are presently unmatched by current technologies, however, dogs still face hurdles of implementation due to lack of inter-governmental cooperation and acceptance by the public health community. Here, we refine the definition of a biomedical detection dog, discuss the potential applications, capabilities, and limitations of biomedical detection dogs in disease outbreak scenarios, and the safety measures that must be considered before and during deployment. Finally, we provide recommendations on how to address and overcome the barriers to acceptance of biomedical detection dogs through a dedicated research and development investment in olfactory sciences.